Carbon and silica megasink in deep-sea sediments of the Congo terminal lobes. (15th October 2019) - Rabouille, C.; Dennielou, B.; Baudin, F.; Raimonet, M.; Droz, L.; Khripounoff, A.; Martinez, P.; Mejanelle, L.; Michalopoulos, P.; Pastor, L.; Pruski, A.; Ragueneau, O.; et al.
Abstract: Carbon and silicon cycles at the Earth surface are linked to long-term variations of atmospheric CO2 and oceanic primary production. In these cycles, the river-sea interface is considered a biogeochemical hotspot, and deltas presently receive and preserve a major fraction of riverine particles in shallow water sediments. In contrast, periods of glacial maximum lowstand were characterized by massive exports of sediments to the deep-sea via submarine canyons and accumulation in deep-sea fans. Here, we calculate present-day mass balances for organic carbon (OC) and amorphous silica (aSi) in the terminal lobe complex of the Congo River deep-sea fan as an analogue for glacial periods. We show that this lobe complex constitutes a megasink with the current accumulation of 18 and 35% of the OC and aSi river input, respectively. This increases the estimates of organic carbon burial by 19% in the South Atlantic Ocean in a zone representing less than 0.01% of the basin. These megasinks might have played a role in carbon trapping in oceanic sediments during glacial times. Highlights: Sediments located at the termination of Congo Canyon are a megasink of organic carbon (0.35 TgC/yr) and aSi (0.11 TgSi/yr). These sediments store in the deep-sea at 5 km depth 18 and 35% of Congo River OC and amorphous silica inputs, respectively. OC burial in these sediments increases OC burial in the South Atlantic deep basin (>3000m) by 19% for a surface area <0.01%. Burial efficiencies in this megasink are 85% for OC and 73% for aSi.